TERMINOLOGICAL ACTIVITY OF THE LEXEME “SUSTAINABLE” IN THE UZBEK ECOLOGICAL DISCOURSE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the terminological activity of the lexeme “sustainable” in Uzbek ecological discourse. It explores its semantic expansion, its role in forming terminological combinations, and its functions in modern communication from linguistic, discursive, and conceptual perspectives.